Rollback recovery in session-based programming - Mezzina, CA; Tiezzi, F; Yoshida, N (Springer, 2023)
To react to unforeseen circumstances or amend abnormal situations in communication-centric systems, programmers are in charge of “undoing” the interactions which led to an undesired state. To assist this task, session-based languages can be endowed with reversibility mechanisms. In this paper we propose a language enriched with programming facilities to commit session interactions, to roll back the computation to a previous commit point, and to abort the session. Rollbacks in our language always bring the system to previous visited states and a rollback cannot bring the system back to a point prior to the last commit. Programmers are relieved from the burden of ensuring that a rollback never restores a checkpoint imposed by a session participant different from the rollback requester. Such undesired situations are prevented at design-time (statically) by relying on a decidable compliance check at the type level, implemented in MAUDE. We show that the language satisfies error-freedom and progress of a session.